The elements of implementing managerial accounting practices in small and medium-sized enterprises - Make, Zain (The Gulf Economist, 2022)
This research aims to shed light on the most important components that facilitate the implementation of management accounting practices by small and medium enterprises, in addition to knowing which of these components has priority in implementing management accounting practices. Of the 70 institutions, 62 valid questionnaires were obtained for statistical analysis. The results showed that one of the most important elements that help small and medium-sized enterprises in implementing management accounting practices are the organizational elements and the business environment of the institution, and that organizational concepts have priority in facilitating the process of implementing practices and then the elements of the environment Business